Arquiteturas da infância: uma construção de memórias - Souza, Kassius Brunno (2024)
Childhood architectures is research that investigates the intersection between childhood and architecture through the body-memory-space relationships and the (re)creation of what I call poeticspatial structures: the house, the church, the school and the street, through artistic practice in different media and languages. The methodology is composed of poetic writing and studio work, driven by the Autobiographical Research in Art approach (Rodrigues, 2021). In this process, I also seek to create dialogues between Bachelard’s (2008) poetics of space and Arfuch’s (2010) biographical space to understand the body of work as a means of establishing a poetics of biographical space. This space is originated, in this research, by fables and daydreams driven by a practice of the self that calls upon writing, childhood, visual arts and architecture to, together, enable the construction of memories.